Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information. Issue 6 (2nd November 2017) - Saito, Eisuke; Khong, Thi Diem Hang
Abstract: Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers' daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers' learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call 'vide-flection' referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children's learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.